Examining the relationships of electronic library individual usage and impact using partial least squares: a formative measurement model - A.K., Razilan; S., Diljit (Malaysian Journal of Library and Information Science, 2017)
Razilan, A. K., & Diljit, S. (2012). Examining the relationships of electronic library individual usage and impact using partial least squares: a formative measurement model. Malaysian Journal of Library & Information Science, Vol.17, no. 2: 1-15. The conceptualisation of individual usage in Information Systems (IS) research is still undergoing debate and development. Despite several conceptualisations and substantial discussions in the literature, the use of formative indicators for constructs’ (latent variables) measurement in empirical studies is still scant. In practice, many of the usage measures were conceptualised as reflective but tested as formative. The partial least squares (PLS) path modelling has in fact rarely been applied in modelling relationships between the posited success constructs in IS research. Only in the early 2000s has the approach gained attention in IS management. In attempting to bridge this gap, this paper examines the relationships between electronic library usage and individual impact where the usage measures were hypothesised as formative measures. It examines the relationships between the individual usage of electronic library for information provisioning and individual impact dimension in an IS Impact model. All of the three hypothesised causal paths among electronic library usage constructs and individual impact tested were supported by PLS.